Criminal law characterization of air pollution - Oliynychuk, Roman (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
The article deals with air pollution. The views of scholars on the legal categories relevant to this offense are analyzed. Scientific positions on air pollution have been covered. The author made a conclusion about air pollution.The author notes about the state of atmospheric air in Ukraine, which is very polluted, causing damage to various living systems. Such changes can affect the person directly or indirectly. They can also adversely affect a person, the life of his body, impair both the physical and chemical properties of the objects he uses, the conditions of his rest and distort the person. Significant concern about the state of the atmospheric air is the impact on it of the “thermal effect” in the biosphere, due to the increase of carbon dioxide in the air. It may be difficult or impossible to list thousands of chemical and biological components that poison the atmosphere. Contamination of individual cities of Ukraine has reached critical levels.The results of the study are an analysis of the current criminal law and the views of scientists on legal categories related to air pollution.According to the author’s position, a more effective way to combat air pollution has been identified.The article concludes that it is necessary to pay special attention to the meager fines for the crime provided for by Art. 241 of the Criminal Code, in comparison with the public danger and the harm caused by this act, we can conclude that the fight against air pollution will be more effective after the responsibility for air pollution in Ukraine is increased. Cash penalties should be increased for both individuals and entities deliberately polluting the air, groundwater or soil.The scientific novelty of the article lies in the implementation of a thorough criminal-law characteristic of air pollution.The practical significance of the results of the study is that the criminal-law characteristics of air pollution can be used in practice to properly qualify a given offense.